Molecular Circuits of Resolution in Airway Inflammation - Troy Carlo; Bruce D. Levy (The Scientific World Journal)
Inflammatory diseases of the lung are common, cause significant morbidity, and can be refractory to therapy. Airway responses to injury, noxious stimuli, or microbes lead to leukocyte recruitment for host defense. As leukocytes respond, they interact with lung resident cells and can elaborate specific mediators that are enzymatically generated from polyunsaturated fatty acids via transcellular biosynthesis. These bioactive, lipid-derived, small molecules serve as agonists at specific receptors and are rapidly inactivated in the local environment. This review will focus on the biosynthesis, receptors, cellular responses, and in vivo actions of lipoxins, resolvins, and protectins as exemplary molecular signaling circuits in the airway that are anti-inflammatory and proresolving.